Relationship counselling for children, young people, and families - Geldard, Kathryn. 4 0 16; Geldard, David; 5 (Los Angeles : Sage, 2009)
An introduction to relationship counseling, covering therapy for parents, whole families, children, and young people, including ways to address parenting issues and an exploration of the issues surrounding confidentiality and the disclosure of inappropriate behaviour.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Family.;Treatment. -- Counseling;Teenagers;Family therapy.;Teenagers.; 20; 2